PERBANDINGAN PERUBAHAN KADAR ANTIGEN SQUAMOUS CELL CARCINOMA PADA KEMOTERAPI PROTOKOL MINGGUAN DAN PROTOKOL TIGA MINGGUAN PADA KARSINOMA SERVIKS UTERI STADIUM LANJUT - , Milhan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: For the treatment of advanced carcinoma of the cervix uteri chemoradiation protocol performed weekly or three weekly. To determine the therapeutic response comparison of both protocols, need to check the tumor marker SCC antigen before and after chemotherapy. Purpose: To determine the ratio of SCC antigen changes before and after the third on the protocol of chemotherapy weekly and three weekly protocol at an advanced carcinoma of the cervix uteri. Methods: The study was performed in RS Sardjito, study subjects were patients with advanced carcinoma of cervix uteri who received chemotherapy protocol weekly or three weekly. Examination of SCC antigen levels before and after the third chemotherapy. Results: There were 30 cases, each of the 15 cases who received weekly protocol and the protocol of three weekly 15 cases. Most 46-55 years old (60.0%) in the weekly protocol and also 60.0% at three weekly protocol. Parity 3 or more, 73.3% and 66.7%. Elementary education level (33.3% and 73.3%). Class III of ward (73.3% and 66.7%). Histopathology of epidermoid carcinoma (40.0%) and squamous cell carcinoma (40.0%). Stage IIB (73.3%) and IIIA (40.0%). At the weekly protocol, the average (mean) SCC antigen levels before treatment (SCC Pre Ag) 8.080 ± 13.151 mg / L and SCC antigen after the weekly protocol (SCC Post Ag) 3.067 ± 3.465 mg / L, with changes (decreased levels) amounting to 5.013 ± 12.000 mg / L. While the protocol three weekly average SCC Pre Ag ± 17.610 21.575 ug / L and Post SCC Ag is 8.074 ± 14.760 mg / L, with changes (decreased levels) for 9.536 ± 14.873 mg / L. With a paired t test individually on a weekly and three weekly protocol obtained: First, there is no change in a significant SCC antigen levels before and after the third on the protocol of chemotherapy weekly. Second, there is a change in a significant SCC antigen levels before and after the third chemotherapy at three weekly protocol. Test done together with the independent t test acquired conclusions: there is no change in a significant SCC antigen levels before and after the third chemotherapy between the weekly protocol and three weekly protocols. Conclusion: there is no change in a significant SCC antigen levels before and after the third chemotherapy between the weekly protocol and three weekly protocols on advanced carcinoma of the cervix uteri.